Exercise-Mediated Neurogenesis in the Hippocampus via BDNF - Liu, Patrick Z.; Nusslock, Robin (Frontiers in Neuroscience, 2018)
Exercise is known to have numerous neuroprotective and cognitive benefits, especially pertaining to memory and learning related processes. One potential link connecting them is exercise-mediated hippocampal neurogenesis, in which new neurons are generated and incorporated into hippocampal circuits. The present review synthesizes the extant literature detailing the relationship between exercise and hippocampal neurogenesis, and identifies a key molecule mediating this process, brain-derived neurotrophic factor (BDNF). As a member of the neurotrophin family, BDNF regulates many of the processes within neurogenesis, such as differentiation and survival. Although much more is known about the direct role that exercise and BDNF have on hippocampal neurogenesis in rodents, their corresponding cognitive benefits in humans will also be discussed. Specifically, what is known about exercise-mediated hippocampal neurogenesis will be presented as it relates to BDNF to highlight the critical role that it plays. Due to the inaccessibility of the human brain, much less is known about the role BDNF plays in human hippocampal neurogenesis. Limitations and future areas of research with regards to human neurogenesis will thus be discussed, including indirect measures of neurogenesis and single nucleotide polymorphisms within the BDNF gene.